Memórias do paradesporto escolar amazonense: uma análise a partir das Paralimpíadas Escolares - Pereira, Pedro Enrique Leles (2023)
The objective of this research was to analyze the history of Amazonian school parasports from the State's participation in the School Paralympics. The methodology includes the use of documentary sources, which are: the official bulletins of the School Paralympics between the 2009 and 2019 editions. From these documents, data were collected, cataloged, interpreted and analyzed. For this purpose, the Document Analysis technique was used. The results showed that the State of Amazonas participated in all editions of the School Paralympics, in the investigated period, possibly signaling efforts towards the development of Paralympic sport in the school bias in the investigated state. 2019 was the year in which Amazonas presented the largest number of members in its guests, with 48 people. In turn, the best performance achieved by the State occurred in 2009, reaching 11th overall in the final classification of the competition. The number of modalities in which the State circumvents with registered athletes/students has gradually increased over the years. On the other hand, the participation of State delegations occurred in less than half of the modalities offered in each edition. It was noted, for example, the dominance of Amazonian athletes/students competing in individual modalities, especially in athletics and swimming. It is concluded that support, appreciation and investments, mainly of a governmental nature, can contribute to the growth and advancement of Amazonian school para-sports, favoring the continued participation of State delegations in the School Paralympics. It is noteworthy that, in addition to opening doors for the social inclusion of people with disabilities through sport, this constitutes an opportunity for the discovery of future Amazonian Paralympic athletes.